Muslimah's Purchase Interest in Halal Cosmetic Products through E-Commerce Platforms: Analysis of Supporting Factors - Afiatna, Fatma Ayu Nuning Farida; Muflihah, Nur; Mayasari, Andhika; Sumarsono, Sumarsono; Nudin, Salamun Rohman (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2025)
This research investigates the various factors that affect the purchasing intentions of Muslim women regarding halal grooming and cosmetic products in an online context. Drawing upon the theory of planned behaviour, the study evaluates how attitudes, subjective norms, and perceived behavioural control contribute to these purchasing intentions. Furthermore, this study examines the role of religiosity as a moderating variable that influences the interplay among attitudes, subjective norms, perceived benefits, and risks in relation to buy intention. Notably, religiosity has demonstrated significant moderating effects across various contexts, encompassing self-regulation, mental health, ethical behaviour, brand compliance, and overall well-being. The observed effect intimates that religiosity possesses the potential to either amplify or mitigate the influence of independent variables on the anticipated outcome, contingent upon the specific contextual nuances and an individual's subjective religious interpretation. Employing a convenience sampling methodology, the research disseminated questionnaires electronically through digital communication platforms including WhatsApp, Telegram, and Facebook, targeting respondents who had attained a minimum age of 18 years. The subsequent data analysis was rigorously conducted utilising Structural Equation Modeling (SEM) via the Partial Least Squares approach (SEM-PLS). The empirical findings reveal a statistically significant correlation among religiosity and the buy intention of halal products, thereby underscoring the profound significance of religious values in shaping the consumer decision-making processes of Muslim women.